2011
DOI: 10.1186/1752-4458-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Communal proactive coping strategies among Tamil refugees in Norway: A case study in a naturalistic setting

Abstract: BackgroundAn exclusive focus on individual or family coping strategies may be inadequate for people whose major point of concern may be collective healing on a more communal level.MethodsTo our knowledge, the current study is the first to make use of ethnographic fieldwork methods to investigate this type of coping as a process in a natural setting over time. Participant observation was employed within a Tamil NGO in Norway between August 2006 and December 2008.ResultsTamil refugees in Norway co-operated to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
2
19
0
7
Order By: Relevance
“…Interestingly, along with reliance on religious support, in our tests of moderation with political violence in the past month, the protective effects of reliance on political support approached significance for both General Health and MH ( B = 27.966, β = .194, p = .092; B = 18.625, β = .178, p = .099, respectively). In line with these findings, research has shown the importance of collective and prosocial forms of coping for both women generally, as well as for survivors of political conflict (Guribye, Sandal, & Oppedal, ; Wells, Hobfoll, & Lavin, ). Findings from our study demonstrate the importance of investigating just how support from institutions, and people's willingness and abilities to ask for help and information from these institutions, factors into the relationship between health and political violence.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, along with reliance on religious support, in our tests of moderation with political violence in the past month, the protective effects of reliance on political support approached significance for both General Health and MH ( B = 27.966, β = .194, p = .092; B = 18.625, β = .178, p = .099, respectively). In line with these findings, research has shown the importance of collective and prosocial forms of coping for both women generally, as well as for survivors of political conflict (Guribye, Sandal, & Oppedal, ; Wells, Hobfoll, & Lavin, ). Findings from our study demonstrate the importance of investigating just how support from institutions, and people's willingness and abilities to ask for help and information from these institutions, factors into the relationship between health and political violence.…”
Section: Discussionmentioning
confidence: 99%
“…In another example, researchers uncovered what they termed "communal proactive coping strategies" that helped Tamil refugees who were survivors of civil war deal with the effects of the war and with resettlement. These communal proactive coping strategies included forming common goals, accumulating shared resources, and establishing new organizations and networks to research and address mental health problems (Guribye, Sandal, & Oppedal, 2011).…”
Section: Community Resiliencementioning
confidence: 99%
“…A este se suma el estudio de Guribye (2011) sobre los factores comunitarios de resiliencia en el pueblo Tamil procedente de la India y asentado en Noruega, del cual se puede concluir que "las comunidades de origen de las personas desplazadas, funcionan como familias sustitutas en el contexto de refugio". (Guribye, 2011citado por Villacieros, 2016. A estos dos estudios sobre solicitantes de asilo y resiliencia en Noruega, en la bibliografía reciente se suma la indagación de Øien y Sønsterudbråten (2011) sobre limitaciones en la movilidad social asociada con el trabajo y la educación en migrantes irregulares, ya citado anteriormente.…”
Section: Estado Del Arte Y Marco Teóricounclassified